Optimizing Conditions for Scandium Extraction from Bauxite Residue Using Taguchi Methodology - Theopisti Lymperopoulou (Minerals, 2019)
Bauxite residue is the voluminous by-product of alumina production after Bayer process. Its high alkalinity causes disposal problems and harmful environmental impacts. However, the residue contains significant amounts of valuable elements, such as rare earth elements, including scandium. Greek bauxite residue contains a high amount of scandium close to its main resources. Taking into account scandium’s limited availability coupled with its high demand in modern technology, bauxite residue could be considered as a potential resource for scandium recovery. In this study, the optimization of scandium extraction from bauxite residue with sulfuric acid is investigated using Taguchi methodology. Based on previous studies, acid molarity, leaching time, solid/liquid ratio, and reaction temperature were selected as control parameters for the selective Sc recovery. Method optimization targeted the highest concentration of scandium combined with the lowest concentration of iron without taking into account application constraints. Maximization of scandium concentration can be achieved only by reduced selectivity. The predicted values resulted from the Taguchi methodology were affirmed by a confirmation experiment conducted at optimal conditions. Regression analysis provided the respective equations to be applied on several conditions, depending on different applications.